Status Kinerja Pengolahan Lingkungan Hidup (SKPL) Limbah B3 Industri Besi PT X, Kota Sidoarjo - Ghany Firmansyah; Mohamad Mirwan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
PT X is an iron industry in Sidoarjo that produces Hazardous and Toxic Material waste. This industry has several Temporary Shelters (TPS) for B3 waste to store its waste. However, supervision based on the regulation of Permen LHK no. 6 of 2021 shows that there are several inconsistencies in B3 waste management and waste storage procedures. This study was conducted to evaluate and determine the correct management of B3 waste, as well as to correct the inconsistencies identified in the SKPL supervision program.